Machine capability sigma level evaluation and allocation method. (July 2020) - Zhang, Sheng-yong; Zhang, Gen-bao; Ran, Yan; Murphy, Adrian
The concept of process capability has been widely used in production management and quality control. However, applying traditional process capability evaluation method to machine capability cannot eliminate the influence of other process factors other than machine. To solve the problem, we propose the sigma machine capability evaluation method in this paper. First, multivariate statistical analysis methods are used to analyze the influence of all factors. Second, we deleted the non-normal data through sample fitting. Then, on the basis of normal distribution, we used the sample variance as the evaluation index to calculate the sigma levels of single characteristic and multiple characteristic parts. Last, we applied the sigma evaluation method and the traditional one to conduct a case study and compare their results, which proves the feasibility and superiority of the sigma level evaluation method.